A Vida e Obra do Professor Doutor Artur Manuel Giesteira de Almeida - Inês Mariana Morais Bento (2021)
Introduction: Professor Artur Manuel Giesteira de Almeida was a notable Portuguese Surgeon and Professor, graduated from the Faculty of Medicine of the University of Porto (FMUP). The following dissertation intends to consecrate this teacher's memory and highlight his contributions in the area of Surgery and in the Faculty to which he dedicated his professional life. Material and methods: a search of the Archive of the Museum of the History of Medicine "Maximiano Lemos" and of the Catalog of the Library of the FMUP was carried out. Interviews were conducted for further clarification. Results: he was born on July 6, 1925, in Porto, and graduated in 1948. He was Assistant to the chair of Clinical Surgery, 1st Assistant and Extraordinary Professor of the 7th Group of FMUP. He held the positions of Regent Teacher of the Chair of Surgical Pathology, Chair of Surgical Clinic and Chair of Operative Medicine of FMUP. Appointed as Director of Operative Medicine of Hospital de São João. He was Full Professor of Surgical Propaedeutics at Surgical University of Lourenço Marques and Clinical Director of the referred Hospital. He was a member of the Northern Regional Council of the Order of Doctors. Named President of the Portuguese Society of Surgery in 1985. He received the 2nd Pfizer Prize in 1964, collaborating with Dr. Ayres Basto. Discussion: Giesteira de Almeida trained and taught generations of great names in portuguese surgery, becoming a highly prestigious personality in his field. Conclusion: he worked until the age of 85, demonstrating his dedication to medicine. He is remembered as a fruitful researcher, a skilled surgeon and, above all, an excellent teacher.